Ecology - Ricklefs, Robert E . (W. H. Freeman, 1999)
Digested, many students find it a difficult subject to grasp. Moreover, the dynamic nature of this discipline presents challenges to providing students with the most current information available. For some time now, instructors have been calling for a textbook that offers just the right balance of subject matter emphasis, clearly presented concepts, and engaging, fresh examples. Ecology authored by ecologists who each have more than 10 years experience teaching the subject is that book. To aid students in integrating material across the levels at which ecology is studied, the book is structured so that they are always reminded of connections among levels of the ecological hierarchy (from individuals to populations to communities to ecosystems) and links to evolution, a unifying theme for all of ecology